Social jetlag affects jump skills in sub-elite volleyball players - Ciorciari, Andrea; Castelli, Lucia; Galasso, Letizia; Mulè, Antonino; Esposito, Fabio; Roveda, Eliana; Montaruli, Angela (Frontiers in Sports and Active Living, 2024)
Social jetlag (SJL),resulting from misalignment between biological rhythms and social schedules,has emerged as a prevalent phenomenon in modern society,particularly among young athletes.However,the effect of SJL on performance is poorly studied.Jump and dynamic balance are two key skills in volleyball,as the first allows the player to perform better both during the offense and defense phase,and the second is fundamental in landing and in injury prevention.Therefore,our aim was to investigate the effect of SJL on jump skill performance and balance in female volleyball players.Thirty female volleyball players (mean age:17.3±0.88 years) participated in the study. SJL was assessed using the Munich ChronoType Questionnaire (MCTQ),integrated with Jankowsky's sleep-corrected formula. Jump skill performance was evaluated using a standardized jump test,the Vertec Jump Test,while balance was assessed with the Y Balance Test.The tests were performed at 09:00a.m. and at 06:00p.m. The results revealed that players with greater SJL exhibited decreased jump performance,characterized by lower vertical jump height (p=0.02).Furthermore,players with lower SJL showed the typical difference between morning and afternoon performance (p=0.001),demonstrating their synchronization between biological rhythms and social commitments,while no statistically significant difference between the two sessions was shown in players with higher SJL.Regarding balance,no significant association with SJL was found,but the morning session yielded lower results than the afternoon one (p=0.01).These findings highlight the detrimental impact of SJL on jump skill performance,underscoring the importance of optimizing sleep-wake schedules and circadian alignment to enhance athletic performance.Future research should explore targeted interventions,such as sleep hygiene education,to minimize social jetlag and promote optimal performance in adolescent athletes.